Influence of Chemotherapy on Allergen-Specific IgE - Whiteside, Sarah; Markova, Marketa; Chin, Alex; Lam, Cynthia; Dharmani-Khan, Poonam; Modi, Monica; Khan, Faisal; Storek, Jan (International archives of allergy and immunology, 2018)
BACKGROUND: Atopy is defined as excess allergen-specific IgE (A-IgE). IgE is produced by plasma cells that differentiate from allergen-specific B cells. B cells are known to be killed by chemotherapy; however, it is not known whether A-IgE-secreting plasma cells are killed or inhibited by chemotherapy. If yes, serum A-IgE levels would be expected to decrease after chemotherapy. OBJECTIVES: We aimed to determine whether A-IgE levels in atopic individuals (serum A-IgE ≥0.35 kUA/L) decrease into the nonatopic range (< 0.35 kUA/L) after chemotherapy. METHODS: In 105 patients undergoing chemotherapy for acute leukemia, we measured serum A-IgE before and after chemotherapy. In a subset of these patients, we also measured B cell counts before and after chemotherapy. RESULTS: Of the 105 patients, 36 were atopic. In these patients, median A-IgE level before chemotherapy was 1.6 kUA/L whereas the median level after chemotherapy was 0.6 kUA/L (p < 0.001). In 12/36 (33%) patients, A-IgE levels decreased into the nonatopic range. In nonatopic patients (n = 69), the median A-IgE level also dropped: from 0.04 kUA/L before to 0.03 kUA/L after chemotherapy (p = 0.001). Among the total patients (n = 105), the median pre:post-chemotherapy A-IgE ratio was 1.8 (2.6 in atopic and 1.5 in nonatopic patients). In contrast, the median ratio of pre:post-chemotherapy B cell counts was 87.6. CONCLUSIONS: A-IgE levels decrease after chemotherapy but markedly less than B cell counts. Thus, at least some A-IgE plasma cells appear to survive chemotherapy.
Keywords: B-lymfocyty; Aged; Immunoglobulin E; lidé středního věku; imunoglobulin E; senioři; B lymphocytes; Antineoplastic Agents; lidé; Adult; Middle Aged; dospělí; B-Lymphocytes; Chemotherapy; Plasma cells; Drug Therapy; Humans; farmakoterapie; IgE; protinádorové látky; Atopy; leukemie; Leukemia